Management of social networks of the audiovisual project EnchufeTv - Suing Ruiz, A. (2016)
In this research work, the management of the social networks of the transmedia project EnchufeTV is analyzed. The methodology is quantitative and qualitative, four monitoring tools of social media ware applied to gather information and collect statistical data between June and July 2015. The research was complemented by interviews to experts in the subject. It can be seen that social media is the ideal platform for new content, viralization and wider dissemination and expansion of the content, although EnchufeTV does not fully exploits the advantages of social media and it does not post in largescale. It is ratified that projects such as EnchufeTV mean a breakthrough in terms of audiovisual content on the Web in Ecuador. © Springer International Publishing Switzerland 2016.